MULTIPLICATIVE LOSS OF LANDLOCKED ATLANTIC SALMON Salmo salar L. SMOLTS DURING DOWNSTREAM MIGRATION TROUGH MULTIPLE DAMS. (1st October 2012) - Norrgård, J. R.; Greenberg, L. A.; Piccolo, J. J.; Schmitz, M.; Bergman, E.
ABSTRACT Relatively little is known about the downstream migration of landlocked stocks of Atlantic salmon Salmo salar L. smolts, as earlier migration studies have generally focused on upstream migration. However, in watersheds with many hydroelectric plants (HEPs), multiplicative loss of downstream‐migrating salmon smolts can be high, contributing to population declines or extirpations. Here we report the results from a study of wild landlocked Atlantic salmon smolts in the River Klarälven. Salmon smolts, tagged with acoustic transmitters, were released at different locations and followed as they passed 37 receivers along a 180‐km‐long river segment, including eight dams as well as free‐flowing control stretches. We found that 16% of the smolts successfully migrated along the entire river segment. Most losses occurred during HEP passages, with 76% of the smolts being lost during these passages, which contrasts with the 8% smolt loss along unregulated control stretches. Migration speed was 83% slower along regulated stretches than along unregulated stretches. The observed lower migration speed at regulated stretches was dependent on fish size, with large fish moving slower than small fish. Discharge affected migration speed but not losses. As previously shown for anadromous populations, our study of landlocked salmon demonstrates similar negative effects of multiple passages of HEPs by downstream‐migrating smolts. On the basis of this and previous migration studies, we advocate using a holistic approach in the management and conservation of migratory fish in regulated rivers, which includes safe passage for both upstream‐ and downstream‐migrating fish. Copyright © 2012 John Wiley & Sons, Ltd.